Pengaruh Pengawasan, Team Work dan Kedisiplinan Terhadap Produktivitas Kerja Karyawan Pada PT Jawamanis Rafinasi Cilegon - Dede Son Aji; H Saefullah; John Chaidir (Amal Insani Foundation, 2023)
The purpose of this study was to determine the effect of supervision, Team Work and discipline together on the work productivity of employees at PT Jawamanis Rafinasi Cilegon. This study used a quantitative approach. As for the population in this study were employees of PT Jawamanis Rafinasi Cilegon, totaling 172 employees, the sample in this study was using simple random sampling calculated based on the Slovin formula so that a sample of 63 employees was obtained. The results of this study in the first hypothesis that there is a significant influence of supervision on work productivity at PT Jawamanis Rafinasi Cilegon obtained tcount > ttable (2.499 > 2.000) with a significance level of less than 0.05. The second hypothesis is that there is a significant effect of team work on product work productivity at PT Jawamanis Rafinasi Cilegon, the results obtained are tcount > ttable (4.508 > 2.000) with a significance level of less than 0.05. The third hypothesis is that there is a significant effect of discipline on work productivity at PT Jawamanis Rafinasi Cilegon, the results obtained are tcount > ttable (3.713 > 2.000) with a significance level of less than 0.05. The fourth hypothesis is that there is a significant influence between supervision, team work and discipline together on work productivity at PT Jawamanis Rafinasi Cilegon, the results obtained are Fcount > Ftable (21.278 > 2.761) with a significance level less than 0.05).